Modelling tree stability in unsaturated soils - Low, Laurence (2018)
Tree stability holds a paramount concern in Singapore where millions of trees were planted around the country. Numerous research works have been done on tree stability but mainly focus on the tree trunk and the tree root architecture. In this study, the focus was on unsaturated soil mechanics. Conventionally, numerical modelling in unsaturated soil was done in two-dimensional analyses due to the limitation of the software. However, tree is a three-dimensional object, using two-dimensional tree model to conduct the simulation may not be accurate. Therefore, three-dimensional tree model using ANSYS is necessary to analyse tree stability in unsaturated soil. SEEP/W and SIGMA/W were used to validate the two-dimensional ANSYS model for steady-state seepage analyse and deformation analyses respectively. Site instrumentation data was then compared with the result obtained by the three-dimensional and two-dimensional ANSYS model. The result showed that the three-dimensional model indeed provided more accurate result compared with the two-dimensional model. Coupled analyses and parametric study were carried out using ANSYS three-dimensional model to study the rainfall effect on tree stability. The result showed that when rainfall intensity reached to. 1.00×10−6 m/s , the force to cause tree failure decreased significantly. Some improvements can be made in future study such as stiffness of soil can be taken into consideration during rainfall as infiltration might change stiffness of soil and cause tree failure.